Some forgotten equilibria of the Bertrand duopoly!? - Mathias Erlei (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2002)
This note analyzes the Bertrand duopoly with constant but asymmetric marginal costs on a market with homogenous products. It is shown that there exist some equilibria that are ignored in the literature on IO. In addition, in this setting (perfectly or nearly perfectly) competitive equilibria exist.
Keywords: D4; L13; 330